Validation of the Spanish Version of the Yale Food Addiction Scale 2.0 (YFAS 2.0) and Clinical Correlates in a Sample of Eating Disorder, Gambling Disorder, and Healthy Control Participants - Granero, Roser; Jiménez-Murcia, Susana; Gearhardt, Ashley N.; Agüera, Zaida; Aymamí, Neus; Gómez-Peña, Mónica; Lozano-Madrid, María; Mallorquí-Bagué, Núria; Mestre-Bach, Gemma; Neto-Antao, Maria I.; Riesco, Nadine; Sánchez, Isabel; et al. (Frontiers in Psychiatry, 2018)
Aims: Due to the increasing evidence of shared vulnerabilities between addictive behaviors and excessive food intake, the concept of food addiction in specific clinical populations has become a topic of scientific interest. The aim of this study was to validate the Yale Food Addiction Scale (YFAS) 2.0 in a Spanish sample. We also sought to explore food addiction and its clinical correlates in eating disorder (ED) and gambling disorder (GD) patients. Methods: The sample included 301 clinical cases (135 ED and 166 GD), diagnosed according to DSM-5 criteria, and 152 healthy controls (HC) recruited from the general population. Results: Food addiction was more prevalent in patients with ED, than in patients with GD and HC (77.8%, 7.8% and 3.3%, respectively). Food addiction severity was associated with higher BMI, psychopathology and specific personality traits, such as higher harm avoidance, and lower self-directedness. The psychometrical properties of the Spanish version of the YFAS 2.0 were excellent with good convergent validity. Moreover, it obtained good accuracy in discriminating between diagnostic subtypes. Conclusions: Our results provide empirical support for the use of the Spanish YFAS 2.0 as a reliable and valid tool to assess food addiction among several clinical populations (namely ED and GD). The prevalence of food addiction is heterogeneous between disorders. Common risk factors such as high levels of psychopathology and low self-directedness appear to be present in individuals with food addiction.